Capture-ELISA for serum IgM antibody to respiratory syncytial virus. - Cevenini, R. (Cambridge University Press, 1986)
A four-component solid-phase capture enzyme immunoassay was set up to test for serum IgM antibody to respiratory syncytial (RS) virus and was compared with immunofluorescence assay (IFA). A total of 128 young children with acute respiratory infections were studied. Thirty-six were shown to be RS virus-positive by the detection of RS virus in nasopharyngeal secretions and 92 were RS virus-negative. A serum specimen was collected after admission to the hospital (days 0-4) and a further specimen was obtained during days 10-14. Out of 36 RS virus-positive patients, 28 (77.7%) were found to be positive for IgM by both capture-ELISA and IFA. Out of 92 RS virus-negative patients 5 (5.4%) were IgM-positive. Four false-positive results were obtained by IFA due to the presence of rheumatoid factor. The capture-ELISA was shown to be a reliable technique in detecting specific IgM antibody to RS virus.